2004
DOI: 10.1177/089686080402400104
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of Peritoneal Dialysis Fluids: Long-term Exposure of Nonuremic Rats

Abstract: Objectives Long-term peritoneal dialysis (PD) leads to structural and functional changes in the peritoneum. The aim of the present study was to investigate the long-term effects of PD fluid components, glucose and glucose degradation products (GDP), and lactate-buffered solution on morphology and transport characteristics in a nonuremic rat model. Methods Rats were subjected to two daily intraperitoneal injections (20 mL/day) during 12 weeks of one of the following: commercial PD fluid (Gambrosol, 4%; Gambro A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 37 publications
1
20
1
Order By: Relevance
“…Although we could not show a strong correlation, the D/P urea and D/P protein values correlated positively with the number of blood vessels in the omentum, with an inverse correlation observed between the D/D 0 glucose values and the number of blood vessels in the omentum. Even though no negative effects of GDP were observed in previous acute rat experiments, with respect to peritoneal solute transport (5,6,19), we found significant differences in the peritoneal permeability between conventional and low‐GDP exposure after 8 weeks of dialysis. The present results suggest that GDP might be the principal mediators of peritoneal neoangiogenesis and subsequent ultrafiltration failure.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Although we could not show a strong correlation, the D/P urea and D/P protein values correlated positively with the number of blood vessels in the omentum, with an inverse correlation observed between the D/D 0 glucose values and the number of blood vessels in the omentum. Even though no negative effects of GDP were observed in previous acute rat experiments, with respect to peritoneal solute transport (5,6,19), we found significant differences in the peritoneal permeability between conventional and low‐GDP exposure after 8 weeks of dialysis. The present results suggest that GDP might be the principal mediators of peritoneal neoangiogenesis and subsequent ultrafiltration failure.…”
Section: Discussioncontrasting
confidence: 95%
“…However, we could not find evidence relating to GDP-containing PDF with peritoneal fibrosis. Other groups have reported that morphological changes in the peritoneal membrane of low-GDP containing PDF treated animals were much less pronounced, including reduced vascular density, preservation of the mesothelial monolayer and intercellular junction, with no reduplication of the submesothelial basement membrane (5), and also found that the presence of GDP could be connected to the mesothelial changes and the increase of fibrosis in specific regions of the peritoneum (6). In addition, peritoneum exposed to standard PDF were characterized by an increased expression of VEGF, microvascular proliferation and submesothelial fibrosis, which were not observed in peritoneum exposed to low-GDP containing PDF (7).…”
mentioning
confidence: 94%
“…As of today, the mechanisms underlying UFF are not completely understood, but the pathological changes of peritoneal biopsies from PD patients indicate that UFF is associated with the PM alterations such as an increase in macrophage infiltration [29], thickness or fibrosis of the submesothelial layer [30–32], and neoangiogenesis [29, 32, 33]. Similarly in rats, a long term of peritoneal exposure to a hypertonic PD solution leads to mesothelial cell damage, fibrosis or increased thickness of PM, and neoangiogenesis, resulting in an increase in lymph flow or loss of fluid removal [3436]. Therefore, any therapy that targets these alterations of the PM will prolong the UF in PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The slides were then differentiated in phosphomolybdic-phosphotungstic acid solution for 15 min, transferred to aniline blue solution and stained for 10 min, and were reacted with 1% acetic acid solution for 5 min. The thickness of the peritoneum, which was defined as the tissue between the mesothelial surface and the underlying muscle or parenchyma, was assessed as previously described [26] . Briefly, the maximal thickness of the peritoneum was measured in three Masson's trichrome-stained tissue sections per rat and five fields, the center of which included the area of maximal thickness, and were examined under ×400 magnification.…”
Section: Methodsmentioning
confidence: 99%